2008
DOI: 10.1097/bpo.0b013e3181653ac8
|View full text |Cite
|
Sign up to set email alerts
|

How Safe Is the Operative Treatment of Gartland Type 2 Supracondylar Humerus Fractures in Children?

Abstract: Therapeutic study, level 4 (case series [no or historical control group]).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 17 publications
8
61
1
3
Order By: Relevance
“…The average age of our patients was similar to that reported in other studies [3,11,32], thus confirming that the incidence of this injury peaks at 3-8 years of age [21]. With respect to the sex distribution, 59% were boys and 41% were girls, and this distribution was the same in both groups of treatments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The average age of our patients was similar to that reported in other studies [3,11,32], thus confirming that the incidence of this injury peaks at 3-8 years of age [21]. With respect to the sex distribution, 59% were boys and 41% were girls, and this distribution was the same in both groups of treatments.…”
Section: Discussionsupporting
confidence: 91%
“…The treatment of type II fractures remains controversial. Whereas most authors prefer surgical treatment [3,8,11,12], others prefer orthopedic treatment [10,14,15]. However, there are few studies that compare the clinical and radiographic outcome with orthopedic or surgical treatment [12,15,16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Twelve to 13 weeks after surgery there was an average loss of 20°and 35°elbow motion in children with and without physical therapy, respectively. In contrast, Skaggs et al [19] observed that at a mean of 8.7 weeks after surgery, 92% (174 of 189) of patients had full ROM and only 1.6% (three of 189) of patients had loss of elbow motion of 10°or greater. However, their study included only Type 2 fractures according to the Wilkins' modification of the Gartland classification for supracondylar fractures of the humerus in children [21], whereas previous studies included Types 2 and 3 fractures.…”
Section: Introductionmentioning
confidence: 90%
“…Reduction of the contracture using two-level shortening osteotomy in the proximal and distal thirds of the forearm bones as a modified Colzi procedure can be a good option for ischemic contracture in certain cases [14]. Postoperative physiotherapy is important to improve residual limb function [15].…”
Section: Discussionmentioning
confidence: 99%